(untitled) (Brazilian Journal of Oceanography, 2020)
The latitudinal variations of the Subantarctic Front (SAF) and Southern Hemisphere atmospheric jet were investigated for the period of 1993-2016. Zonal wind velocity, sea surface height and temperature data were used to identify these features over the South Atlantic, South Pacific and Indian Oceans individually. During this period, the atmospheric jet migrated poleward 0.34°S decade-1 in the Atlantic, 0.28°S decade-1 in the Pacific and 0.14°S decade-1 in the Indian oceans. Previous works have shown that the poleward trend is due to the expansion of the tropical belt as a consequence of greenhouse gas increase and cooling of polar stratosphere due to ozone depletion. In addition the atmospheric jet strengthen in all three basins. The SAF represents the Antarctic Circumpolar Current northern boundary and was observed in average at 46.3°S (±0.5°) in the Atlantic, 54.3°S (±0.3°) in the Pacific and 46.6°S (±0.5°) in Indian Oceans. The SAF shows a poleward migration of 0.46°S decade-1 in the Atlantic, 0.20°S decade-1 in the Pacific and 0.27°S decade-1 in the Indian Oceans, which is attributed to the sea level increasing in the Southern Hemisphere due to thermal expansion. The SAF poleward trend is consistent with the positive trend of the Southern Annular Mode during the studied period. Moreover, the jet position is statistically significant correlated to the SAF position in each ocean basin. However, the coefficients are weak: +0.22 for the Atlantic, +0.17 for the Pacific and +0.21 for the Indian oceans. The latitudinal displacement of the SAF in the Pacific is inversely proportional to the El Niño-Southern Oscillations (ENSO). During El Niño years the SAF tend to be more poleward and during La Niña years more equatorward, with maximum correlation of 0.56, with ENSO leading by three months.